The Effects of Curcumin Administration on Carotid Intima-Media Thickness and Pulse Wave Velocity in Diabetic Hemodialysis Patients: A Randomized, Double-Blinded, Placebo-Controlled Trial - Mojtaba Ghasemiadl; Soheil Ghasemi; Alireza Soleimani; Mahsa M Esfahani; Javid Azadbakht; Hamid R Gilasi; Hamid R Talari (International Journal of Preventive Medicine, 2024)
Background: Prior studies have reported that curcumin is inversely associated with reduced markers of atherosclerosis risk, including carotid intima-media thickness (CIMT). This study was designed to assess the effects of curcumin on CIMT and pulse wave velocity (PWV) in diabetic hemodialysis (HD) patients. Methods: This randomized, double-blinded, placebo-controlled trial was conducted on 39 diabetic HD patients. People were assigned to receive curcumin or placebo (starch) for 24 weeks. Individuals in the curcumin group (n = 26) received 80 mg/day. CIMT and PWV levels were taken at baseline and after 24 weeks of intervention. Results: After 24 weeks of intervention, curcumin intake did not affect mean levels of left (P = 0.83) and right (P = 0.47) CIMT and maximum levels of left (P = 0.84) and right (P = 0.11) CIMT, and PWV (P = 0.12) compared to the placebo. Furthermore, within-group difference demonstrated a significant reduction in mean levels of PWV (P = 0.01) in the curcumin group. We did not observe any significant change in C-reactive protein (CRP) concentrations after curcumin intake (P = 0.69). Conclusions: Curcumin intake did not affect mean levels of left and right CIMT and maximum levels of left and right CIMT, PWV, and CRP levels compared to the placebo. Additionally, within-group difference demonstrated a significant reduction in mean levels of PWV in the curcumin group. This trial was registered at www.irct.ir as http://www.irct.ir: IRCT20200527047584N1.